WATER SUPPLY AND ITS RELATION TO DIARRHOEAL DISEASES - Kishore, Surekha; Garg, B S; Muzammil, K (Indian Journal of Community Health, 2009)
Background: As per WHO estimates, 80% of all the diseases in developing countries including India are related to unsafe drinking water and poor sanitation. Water pollution is invariably high in community wells. As such, incidence of diarrhoeal diseases is more in the rural set up and can be partly attributed to this. About 40% of the population does not have access to safe drinking water. Objective: To establish a relationship between water supply and incidence of diarrhoeal diseases. Methods: A cross-sectional study was conducted in Sawli village, District Samudrapur (Maharashtra). The study group comprised of 75 under five children, selected by simple random sampling. Data was collected on a pre-designed questionnaire by interviewing the mothers and was analyzed using an appropriate statistical package. Results: Prevalence ofdiarrhoea was found out to be 71 %. only 8% ofthe children who were exclusively breast-fed had any episode of diarrhea. Incidence of diarrhea was high in cases that were drawing water from open wells i.e. 65.3%. Only 28.5% cases reported diarrhea and were drawing water from sanitaiy wells as against 80.32% who took water from insanitary welts. About 45.33% mothers had wrong beliefs about thecauses of diarrhea. ORSwas used in only 30.66% of the cases as a treatment modality. Conclusions: Diarrhoeal incidence was significantly high in children below 3 years of age, prevalence was least in exclusively breast fed